RANCANG BANGUN ALAT BANTU NAVIGASI BAGI PENYANDANG TUNANETRA MENGGUNAKAN ESP CAM DAN SENSOR TOF DENGAN METODE IMAGE PROCESSING - Kurniawan, Beni; Nurussa’adah, n/a; Rahmadwati, n/a (Jurnal Mahasiswa TEUB, 2024)
The sense of vision plays a crucial role in daily activities, with 80-85% of information being received through sight. Visually impaired individuals face challenges in mobility and accessing information, particularly because aids such as canes cannot effectively detect or classify objects. According to data from WHO (2019) and the Indonesian Ministry of Health (2018), millions of people worldwide, including in Indonesia, experience visual impairments. This study designs a navigation aid for visually impaired individuals using an ESP Cam and a ToF sensor integrated with an ESP32-S3 microcontroller to detect and classify objects around the user. Testing results show high detection accuracy for backgrounds (99%) and stairs (100%), but improvements are needed for detecting humans (33.3%) and chairs (25%). The ToF sensor successfully detected distances with a low average error (0.1 cm) and a small standard deviation (0.78 cm), making the device reliable in supporting the mobility of visually impaired individuals.Keywords: Visually Impaired, Assistive Device, ESP Cam, ToF Sensor, Image Processing